(untitled) (Ustozlar uchun, 2026)
This article analyzes the relationship between English and professions in technical schools and its role. Learning English in the process of vocational education helps to understand modern technologies, work with international resources, and develop professional skills. It also highlights how language knowledge increases competitiveness in the labor market.